2010
DOI: 10.1021/ol902776d
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Total Synthesis of Otteliones A and B

Abstract: Enantioselective total synthesis of otteliones A and B was accomplished. The key steps are radical cyclization of an alpha-iodoketone to construct the cis-hydrindanone skeleton and Suzuki-Miyaura coupling to incorporate the aromatic group. (+)-Ottelione A was converted to (-)-ottelione B on treatment with NaOH in THF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Compound 4 and its C-1 desvinyl derivative 11a, C-7 methylene derivative 19, and C-7 exocyclic ethylidene derivative 23 were assayed first (Table 1). Enantiomerically pure 4, prepared according to our published method, 21 showed strong inhibition of the growth of the cancer cells with IC 50 values of 0.40−92.8 nM; the results are consistent with the reported potency of 4 from natural 12 and synthetic sources. 17 The cells most sensitive toward 4 were HCT-116 and A375 cells, which were inhibited at subnanomolar concentrations (IC 50 , 0.74 and 0.40 nM, respectively).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Compound 4 and its C-1 desvinyl derivative 11a, C-7 methylene derivative 19, and C-7 exocyclic ethylidene derivative 23 were assayed first (Table 1). Enantiomerically pure 4, prepared according to our published method, 21 showed strong inhibition of the growth of the cancer cells with IC 50 values of 0.40−92.8 nM; the results are consistent with the reported potency of 4 from natural 12 and synthetic sources. 17 The cells most sensitive toward 4 were HCT-116 and A375 cells, which were inhibited at subnanomolar concentrations (IC 50 , 0.74 and 0.40 nM, respectively).…”
supporting
confidence: 87%
“…21 The bicyclo[4.3.0]nonane core structure was constructed via radical cyclization. The C-3 3′-hydroxy-4′-methoxyphenylmethyl group, C-1 vinyl group, and C-7 exocyclic double bond were then sequentially introduced.…”
mentioning
confidence: 99%
“…Synthetic strategy: Sha et al reported the fourth total synthesis of (+)-1 and (−)-2 in 2010 [20]. Their retrosynthetic analysis is illustrated in Scheme 14.…”
Section: Sha's Total Synthesismentioning
confidence: 99%
“…In the following year, Mehta and our groups independently achieved the first enantioselective total synthesis of naturally occurring (+)-1 and (−)-2, leading to the establishment of their absolute configurations [15][16][17]. Recently, two additional total syntheses of (+)-1 and (−)-2 were reported by Clive et al in 2007 [18,19] and Sha et al in 2010 [20], respectively. In addition, the formal total synthesis of (+)-1 and (−)-2 was also reported by Ryu et al in 2008 [21].…”
mentioning
confidence: 99%
See 1 more Smart Citation